Making elections work: campaign cash, marketisation of votes and social negotiation in India - Mitra, Subrata Kumar; Pohlmann, Markus (Political corruption and organizational crime, 2021)
Free, fair and orderly elections, and significant popular participation are the sine qua non of a robust democracy. And votes which are neither ‘bought’ nor coerced, are vital for legitimacy of the democratic process. At the first sight, Indian democracy appears to deviate from this norm. However, the country has had regular, generally free and fair elections, over past seven decades, conducted and closely supervised by the independent Election Commission of India. The chapter analyses this puzzling co-existence of illegal campaign financing and the resilience of electoral democracy.
Gesehen am 17.12.2021